2015
DOI: 10.1590/1982-0224-20130212
|View full text |Cite
|
Sign up to set email alerts
|

Diet shift of Red Belly Pacu Piaractus brachypomus (Cuvier, 1818) (Characiformes: Serrasalmidae), a Neotropical fish, in the Sepik-Ramu River Basin, Papua New Guinea

Abstract: Introduction of fish species is a globally widespread practice that causes losses of native species and homogenization of diversity within and across continents. Diet assessments are important tools to depict the ecological function of species introduced into novel ecosystem and possible direct and indirect ecological effects. In this study, we compare the diet of Piaractus brachypomus, a mainly frugivorous Neotropical fish, introduced into the Sepik-Ramu River Basin (Papua New Guinea) nearly two decades ago, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The teeth of Pacu are adapted for cracking open the hard shells of nuts and seeds. Despite being mostly vegetarian during the growth period, the adults will feed on smaller animals such as insects, smaller fish and even mammalian body parts, as pointed by gut content analysis of Red Bellied Pacu from the Sepik-Ramu River Basin, Papua New Guinea (Sandra Bibiana Correa et al, 2015). The stomach content analysis of Red Bellied Pacu revealed that the main food was plants or detritus matters and fruits as per the above mentioned study.…”
Section: Scientific Classificationmentioning
confidence: 66%
“…The teeth of Pacu are adapted for cracking open the hard shells of nuts and seeds. Despite being mostly vegetarian during the growth period, the adults will feed on smaller animals such as insects, smaller fish and even mammalian body parts, as pointed by gut content analysis of Red Bellied Pacu from the Sepik-Ramu River Basin, Papua New Guinea (Sandra Bibiana Correa et al, 2015). The stomach content analysis of Red Bellied Pacu revealed that the main food was plants or detritus matters and fruits as per the above mentioned study.…”
Section: Scientific Classificationmentioning
confidence: 66%
“…Piaractus brachypomus was the only species of Characiformes in which all fish captured had seeds in the digestive tract. A study carried out by Correa, Betancur-R, de Mérona, and Armbruster (2014) showed that fruits and seeds are the dominant items in the diet of this species during the flood period, since young and adult specimens are highly adapted to exploit this food source (Lucas, 2008). The contribution to the seed dispersal by P. brachypomus and C. macropomum was investigated by Anderson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent diet shifts among frugivorous fishes have been reported in response to translocation (e.g., Piaractus brachypomus, Serrasalmidae; Correa et al. 2014 ) or hydrological alteration after damming (e.g., Mylossoma duriventre, Serrasalmidae , Brycon gouldingi and B. falcatus, Bryconidae; Albrecht et al. 2009 , Melo et al.…”
Section: The Flood Pulse and Its Changementioning
confidence: 99%